THE VULNERABILITY OF PROVING FRAUD AS THE BASIS FOR CANCELLING AGREEMENTS IN THE DIGITAL ERA - Siombo, Marhaeni Ria (Faculty of Law Universitas Padjadjaran, 2023)
Civil Law grants freedom to everyone to agree on something as long as it fulfills the valid agreement requirements stated in Article 1320 of the Civil Code. The consent condition is mentioned in Article 1321 of the Civil Code. Consent is invalid if there is a mistake, coercion, or fraud. This writing discusses consent that is not valid due to fraud. Article 1328 of the Civil Code states that 'fraud is a reason for the cancellation of an agreement if the deception used by one of the parties is so obvious and clear that the other party would not have agreed if there was no deception.' It is not easy to prove fraud in an agreement that has been made, as the party that feels deceived is not in a position of 'being forced' and voluntarily signs or digitally approves the agreement with a submitted or accepted mark. More detailed regulations regarding canceling agreements due to fraud are needed to provide legal certainty and justice for the parties.